ANALISIS PERLAKUAN AKUNTANSI ASET TETAP PADA PT. MASSINDO SINAR PRATAMA MANADO - Noe, Nurjana; Tinangon, Jantje; Elim, Inggriani (GOING CONCERN : JURNAL RISET AKUNTANSI, 2014)
The rapid implementation of development in various industry sectors, supported by advances in technology and the globalization of international markets will have an impact on the onset of intense competition among enterprises, especially those engaged in the industry. PT. Massindo Sinar Pratama is a private company which is in Manado, North Sulawesi engaged in manufacturing. To be able to support and facilitate the operations of the company's fixed assets required. The role of fixed asset accounting is required by the decision. The purpose of this study was to assess the extent to which the company has applied the theory in accordance with Statement of Financial Accounting Standards (SFAS) no. 16. This study used a descriptive - comparative method of analysis. In this study only focused on fixed assets engines. The results showed that the recognition, measurement, after the acquisition of fixed assets expenses, depreciation of fixed assets and fixed asset presentation, PT. Massindo Sinar Pratama Manado applying accounting policies that have led to to the Statement of Financial Accounting Standards (SFAS) No. 16